Relationship between small dense low density lipoprotein and cardiovascular events in patients with acute coronary syndrome undergoing percutaneous coronary intervention - Jianwei Zhang; Lingjie He (BMC Cardiovascular Disorders, 2021)
Abstract Background Residual risk remained significant despite effective low density lipoprotein cholesterol (LDL-C) lowering treatment. Small dense low density lipoprotein cholesterol (sdLDL-C) as part of LDL-C has been found to be predictor of coronary heart disease (CHD) and cardiovascular (CV) events in patients with stable CHD independently of LDL-C. However, to date, few studies have explored the role of sdLDL-C in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary intervention (PCI). Accordingly, this study aimed to evaluate the association of sdLDL-C with CV events in patients with ACS undergoing PCI. Methods Patients hospitalized with ACS undergoing PCI were enrolled and followed up for 18 months. The risk of sdLDL-C for CV events was compared according to sdLDL-C quartiles. The primary outcome was major cardiovascular and cerebrovascular adverse events (MACCE), which was the composite of all cause of death, nonfatal myocardial infarction (MI), nonfatal stroke or unplanned repeat revascularization. A Cox proportional hazards regression model was performed to estimate the risk of CV events. Subgroup analysis according to diabetes status and LDL-C were performed separately for MACCE. Results A total of 6092 patients were included in the analysis (age: 60.2 ± 10.13 years, male: 75.3%, BMI: 25.9 ± 3.33 kg/m2, dyslipidemia: 74.1% and diabetes: 44.5%). During 18 months of follow-up, 320 (5.2%) incident CV events occurred. Compared to the lowest sdLDL-C quartile group, patients in the highest quartile had a greater risk of CV events after multivariable adjustment (HR 1.92; 95% CI 1.37–2.70). In addition, it was mainly due to the increase of unplanned repeat revascularization. In the subgroup analyses, significant association was observed regardless of level of LDL-C and diabetes status. Conclusions Patients with elevated sdLDL-C have a higher risk of CV events in Chinese patients with ACS undergoing PCI, providing additional value for better risk assessment.